Detailed investigation and analysis of the dynamic evolutionary process of rainstorm debris flows in mountain settlements: a case study of Xiangbizui Gully - Cai, Jiajun; Huang, Wenjie; Yang, Quanzhong (Frontiers in Earth Science, 2023)
Short-term heavy rainfall often causes large-scale rainstorm debris flows in mountainous areas of Southwest China. Aiming to investigate the accumulation and movement of potential source material for the formation of debris flow hazards under extreme short-term heavy rainfall, this paper takes the Xiangbizui debris flow gully, Southwest China, as a case study. A detailed field engineering and geological investigation was carried out on the valley characteristics, formation conditions, provenance types, distribution range, loose solid material reserves that can be transformed into debris flows, and characteristics showing the variation in the grain size of the accumulated solids along the gully to further explore the characteristics of rainstorm-induced debris flow movement. The dynamic processes of debris flow movement and accumulation are numerically simulated to analyze the maximum velocity, accumulation height, range of influence, and evolutionary process based on the theory of continuous media of the approximate Voellmy solution and a high-precision three-dimensional model. The results indicated that rainstorms and steep terrain are the main factors stimulating debris flows. The amount of loose solid material in the channel is approximately 1550.61 × 104 m3, and the dynamic material reserves are approximately 396.41 × 104 m3. The maximum flow depth and velocity are approximately 3.5 m/s and 13 m/s, respectively, which mainly occur in the upper and middle reaches of the channel and in the accumulation fan at the outlet of the channel. The evolutionary process of the debris flow includes four stages: a 0–1,500 m initial acceleration stage, a 1,500–2,200 m fast forward movement stage, a 2,200–3,400 m acceleration stage in the middle and lower reaches, and a 3,400–4,300 m deceleration and end of accumulation stage. The research findings can provide a scientific basis and strong support for risk assessment and avoidance, as well as prevention and control of debris flows in mountainous areas with severe climate change.